Atomistic mechanism underlying shock-induced phase transition in HfNbTaTiZr energetic high-entropy alloy - Xiang-yu Meng; Lei Zhang; Hai-ying Wang; Lan-hong Dai (Energetic Materials Frontiers)
Energetic high-entropy alloys (HEAs), known for their exceptional mechanical properties and high energy density attributes, have attracted significant attention in energetic structure materials. However, these alloys typically operate under shock loadings, and the induced phase transitions occur at ultra-high strain rates, surpassing the resolution capabilities of current experimental equipment. The interplay of varying elemental compositions and short-range order further complicates the phase transitions, leaving the underlying mechanisms poorly understood. In this study, hybrid molecular dynamics and Monte Carlo (MD/MC) simulations were conducted to investigate the atomistic mechanism of shock-induced phase transitions in a prototypical energetic HEA Hfx(NbTaTiZr)(1-x), considering variations in Hf element contents and degrees of chemical short-range order (CSRO). It was found that shocked HfNbTaTiZr undergoes a structural transition from its initial body-centered cubic (BCC) phase to a hexagonal close-packed (HCP) phase. This transition was predominantly facilitated by the decrease in atomic spacing along the shock direction, an increase in atomic spacing perpendicular to it, and the slip of certain (1‾ 10) planes along the [1‾1‾ 0] crystallographic direction. The shock velocity thresholds of HCP nucleation and growth were determined to be 230 m s−1 and 280 m s−1, respectively. An increase in Hf content lowered the threshold for the BCC to HCP phase transition, while CSRO reduced the nucleation threshold of HCP but increased the growth threshold. Finally, a physical model was developed to quantify the interplay between Hf content and CSRO in regulating the initiation and evolution of phase transition in shocked Hfx(NbTaTiZr)(1-x). These findings will shed new light on the understanding of shock-induced phase transitions in energetic metallic materials.